1997
DOI: 10.12968/bjom.1997.5.3.144
|View full text |Cite
|
Sign up to set email alerts
|

Choice of a scan: how much info do women receive before ultrasound

Abstract: In order to discover the amount of information given to women so that they can make a choice as to whether to have a scan or not, a questionnaire was sent to 100 maternity units. Ninety-four units responded; out of these a subsample of 45 were sent a further, more detailed questionnaire. Analysis of the results revealed that 48% of the initial sample units gave information to women of the scan's potential to detect anomalies; of these only 26% gave the information before the first scan. Eighty-three per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A survey of midwives and obstetricians carried out by the same team found gaps in staff knowledge about antenatal screening (25). A survey of United Kingdom hospital practice reported that just under one‐half the maternity units surveyed routinely gave women information about the potential of a scan to detect anomalies (26).…”
Section: What Do Women Know About Reasons For Using Ultrasound and Whmentioning
confidence: 99%
“…A survey of midwives and obstetricians carried out by the same team found gaps in staff knowledge about antenatal screening (25). A survey of United Kingdom hospital practice reported that just under one‐half the maternity units surveyed routinely gave women information about the potential of a scan to detect anomalies (26).…”
Section: What Do Women Know About Reasons For Using Ultrasound and Whmentioning
confidence: 99%
“…Women who experience distress and unrealistic perceptions may benefit from interventions designed to lessen these states2. Interventions including various information aids3, psychological support5, and two‐dimensional (2D) ultrasound examination6–14 have been studied. Although some studies in the early 1980s failed to demonstrate a significant effect of a 2D ultrasound examination on the attitude of low‐risk women towards the fetus and on maternal anxiety6, 7, other studies have shown that 2D ultrasonography allows recognition of the unborn baby and reassurance of fetal well‐being, which reduces maternal anxiety in women at both low8, 9 and high risk of fetal anomalies10–12.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies in the early 1980s failed to demonstrate a significant effect of a 2D ultrasound examination on the attitude of low‐risk women towards the fetus and on maternal anxiety6, 7, other studies have shown that 2D ultrasonography allows recognition of the unborn baby and reassurance of fetal well‐being, which reduces maternal anxiety in women at both low8, 9 and high risk of fetal anomalies10–12. 2D ultrasound also stimulates a parental bond with the fetus and contributes to positive health behavior13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 Most women being offered these scans are at low risk of fetal abnormality and the scan constitutes their first visual encounter with their baby. They may believe that it will provide information only about gestational age and be unaware of the range of abnormalities that can be detected.…”
mentioning
confidence: 99%
“…They may believe that it will provide information only about gestational age and be unaware of the range of abnormalities that can be detected. Recent research suggests that many women are not told beforehand of the first scan's potential to detect fetal anomalies,4 and several letters in this week's issue add further evidence (p 748). Many women whose pregnancies may have naturally ended in spontaneous perinatal loss are thus being faced with having to make an active decision about whether to continue with their pregnancy.…”
mentioning
confidence: 99%